Factors associated with cognitive impairment during the first year of treatment for nonmetastatic breast cancer. (16th January 2021) - Rodriguez, Nicole; Fawcett, Jonathan M.; Rash, Joshua A.; Lester, Renee; Powell, Erin; MacMillan, Connor D.; Garland, Sheila N.
Abstract: Background: Women with breast cancer are more likely to develop cognitive impairment (CI), insomnia, fatigue, and mood disturbance than individuals with other cancers. The main objectives of this study were to establish the prevalence of CI and examine the relationships between CI, insomnia, fatigue, and mood over the first year of breast cancer treatment. Methods: Participants were recruited after diagnosis and completed validated measures of insomnia, objective and perceived CI, fatigue, and mood disturbance at four time points during the first year of treatment. A random intercepts cross‐lagged panel model assessed relationships among symptoms over time. Results: The sample included 98 women. Prevalence of objective CI ranged from 3.1% to 8.2% throughout the year, whereas 36.7% demonstrated a clinically meaningful decline in perceived CI from baseline to 4 months, which remained relatively stable. Greater perceived CI was associated with more fatigue ( β  = −0.78, z  = 17.48, p  < .01) and symptoms of insomnia ( β  = −0.58, z  = 5.24, p  < .01). Short‐term fluctuations in perceived CI ( p  < .05), but not fatigue or insomnia, predicted future perceived CI. Fatigue ( p  < .001) was a significant predictor of future reported symptoms of fatigue and insomnia. Conclusion: Subjective CI is more prevalent than objective impairments. Fatigue, insomnia, and perceived CI remain stable and are associated during the first year of treatment. Changes in insomnia and fatigue may have little effect on future perceived cognition. Women with breast cancer likely require targeted intervention for these side effects. Abstract : This study recruited 98 women with non metastatic breast cancer shortly after diagnosis and assessed their objective and perceived cognitive function alongside their levels of insomnia, fatigue, and mood disturbance at 4 time points: shortly after diagnosis and 4 months, 8 months, and 12 months later. Subjective impairment was more prevalent than objective impairment and both remained stable across the year. Perceived impairment in cognition was associated with fatigue and insomnia symptoms, suggesting the need for interventions that can address co‐occurring symptoms.